Community water fluoridation exposure and dental caries experience in newly enrolled members of the Canadian Armed Forces 2006–2017 - Batsos, Constantine (Can J Public Health, 2021)
OBJECTIVES: This cross-sectional study examines the dental caries experience of new Canadian Armed Forces (CAF) members in relation to enrollment from municipalities with and without water fluoridation. METHODS: The study population consisted of recruits who enrolled in the CAF between 2006 and 2017 with an enrollment address in municipalities with known fluoridation status (n = 24,552). Odontogram statistics from dental examinations were used to calculate the number of decayed, missing, and filled teeth (DMFT) and tooth surfaces (DMFS) for each recruit. The average difference between recruits from municipalities with and without fluoridation was determined using a linear regression model which adjusted for confounding by age and gender and allowed effect modification based on socio-economic status. RESULTS: The average recruit was male, 24 years of age, with 5.6 DMFT and 11.6 DMFS. After adjusting for age and gender, recruits residing in municipalities with water fluoridation had lower DMFT by 0.67 (CI − 0.55, − 0.79) points and lower DMFS by 1.77 (− 1.46, − 2.09) points. When allowing for effect modification by median income quintile of the recruits’ home census tract, the average reduction in DMFT and DMFS was similar in all income quintiles, with average reductions in DMFT ranging from 0.47 to 1.02 and average reductions in DMFS ranging from 1.33 to 2.70. CONCLUSION: Residence in a municipality with water fluoridation was associated with reduced caries experience in a national sample of newly enrolled CAF members. The benefits of water fluoridation were uniform across neighbourhood income and military rank classes.